2013
DOI: 10.1111/dsu.12123
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of a Focused Ultrasound Device for Treatment of Adipose Tissue in Subjects Undergoing Abdominoplasty: A Placebo-Control Pilot Study

Abstract: High-intensity focused ultrasound treatment was well tolerated and safe. Focal damage to target tissue was documented, with adjacent tissues remaining intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…However, despite many individual – often only anecdotal – user reports, only a minority of methods is proven according to the evidence-based medicine standards. Such evidence is available for efficacy of chemical lipolysis, based on injection of phosphatidylcholine and deoxycholic acid 9 , and for selected energy-based technologies using focused ultrasound 10 , cryolipolysis 11 and/or thermal/radiofrequency for lipolysis 12 . Despite the broad use in the practice, clinical safety data of these aesthetic procedures are scarce, with only a few publications available 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, despite many individual – often only anecdotal – user reports, only a minority of methods is proven according to the evidence-based medicine standards. Such evidence is available for efficacy of chemical lipolysis, based on injection of phosphatidylcholine and deoxycholic acid 9 , and for selected energy-based technologies using focused ultrasound 10 , cryolipolysis 11 and/or thermal/radiofrequency for lipolysis 12 . Despite the broad use in the practice, clinical safety data of these aesthetic procedures are scarce, with only a few publications available 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In one application, ultrasound has been used alongside laser facial resurfacing to enhance transdermal cosmeceutical delivery [114]. Another cosmetic application that has been tested in humans is body sculpting, where high intensity FUS is used to ablate adipose tissue that is then later resorbed [115]. A randomized, sham-controlled body sculpting study found no difference in adverse events in the treated and sham groups at 24 week follow-up, suggesting that the treatment is safe [116].…”
Section: Cosmeticmentioning
confidence: 99%
“…The combination of a mechanical effect, that disrupts the cell membranes immediately, and a thermal mechanism, that destroys adipocytes at temperatures above 58°C, causes coagulative necrosis within a small targeted area while the surrounding tissue remains mostly unaffected 2. Studies have shown evidence of fat necrosis3 and an average reduction in waist circumference of more than 2 cm 12 weeks after a single treatment 4…”
Section: Body Contouring Techniquesmentioning
confidence: 99%